2008
DOI: 10.21273/jashs.133.3.462
|View full text |Cite
|
Sign up to set email alerts
|

Expansin and XET Genes Are Differentially Expressed During Aril Breakdown in Harvested Longan Fruit

Abstract: Fresh fruit of longan (Dimocarpus longan Lour.) are susceptible to pericarp browning and aril breakdown. Aril breakdown in longan fruit is regarded as one of the most important factors reducing quality and shortening storage life of the fruit. To better understand the molecular mechanism of aril breakdown, the expression patterns of three expansin (EXP) and three xyloglucan endotransglucosylase (XET) genes in relation to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Alpha-expansin ( EXP ; MDP0000785413, MDP0000259640) also showed high expression in the affected outer cortex. An increased expression of both XET s and EXP s has been implicated in aril breakdown of longan ( Dimocarpus longan ) fruit stored at low temperature [ 43 ]. Two cell wall pectin esterases, an auxin-repressed pectin-lyase (MDP0000171438) and a pectinacetylesterase (MDP0000162976) were induced in the affected outer cortex.…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-expansin ( EXP ; MDP0000785413, MDP0000259640) also showed high expression in the affected outer cortex. An increased expression of both XET s and EXP s has been implicated in aril breakdown of longan ( Dimocarpus longan ) fruit stored at low temperature [ 43 ]. Two cell wall pectin esterases, an auxin-repressed pectin-lyase (MDP0000171438) and a pectinacetylesterase (MDP0000162976) were induced in the affected outer cortex.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of reducing sugars was determined by using dinitrosalicylic acid reagent [17]. The absorbance at 540 nm was measured and compared to a standard curve of glucose to determine the concentration of reducing sugars.…”
Section: Enzymatic Hydrolysis Activity Assay Of Cellulosementioning
confidence: 99%
“…XTHs were previously thought to be responsible for fruit softening and textural changes during storage by breaking down the cellulose-xyloglucan matrix and loosening the cell wall, as has been described in fruits, such as apple (Munoz-Bertomeu et al, 2013 ), longan (Feng et al, 2008 ; Zhong et al, 2008 ), grape berry (Ishimaru and Kobayashi, 2002 ), lychee (Lu et al, 2006 ), and tomatoes (Saladie et al, 2006 ; Miedes and Lorences, 2009 ). However, some authors reported that XET activity could be associated with the maintenance of structural integrity of the cell wall rather than for dismantling it (Hiwasa et al, 2004 ; Fonseca et al, 2005 ; Nishiyama et al, 2007 ; Miedes et al, 2010 ).…”
Section: Introductionmentioning
confidence: 96%